Effect of Nutritional Education, Fibre Food Source and Physical Activity on Nutritional Status of Obese Students in Integrated Islamic Elementary School, Bogor - Verawati, Besti; Madanijah, Siti; Syarief, Hidayat (Pakistan Journal of Nutrition, 2016)
The aim of the study was to analyze the effect of nutritional education, physical activity and dietary fibre intake on nutritional status of obese students in integrated Islamic Elementary School, Bogor. Quasi-experimental study design was used with a total of 84 students from three integrated Islamic elementary school in Bogor as samples. The samples were divided into three groups, group A with nutritional education and physical activity intervention, group B with nutritional education and fibre source interventions and group C with nutritional education, physical activity and fibre source interventions. The results indicated that nutritional knowledge and fibre intake increased in all, physical activity increased in group A and C and Body Mass Index (BMI) by age decreased in all groups. Paired sample t-test indicated that nutritional knowledge and fibre intake between three groups were significantly different (p